2022
DOI: 10.1186/s41043-022-00322-w
|View full text |Cite
|
Sign up to set email alerts
|

The association of food insecurity and cardiometabolic risk factors was independent of body mass index in Iranian women

Abstract: Background Investigations on food insecurity have shown that food insecurity is inversely associated with health. We examined the association of food insecurity and cardiometabolic risk factors in women living in Shiraz, Iran. Methods The cross-sectional study was performed on 190 females. Food insecurity was assessed by Household Food Insecurity Access Scale. Cardiometabolic risk factors including anthropometric characteristics, blood pressure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The association between food insecurity and cardiometabolic risk factors was explored in a study conducted in Iran (Hashemzadeh et al, 2022). The study found that cardiometabolic risk factors, such as blood glucose, triglycerides, total, HDL, and LDL cholesterols, and metabolic syndrome score, were associated with food insecurity independent of body mass index (BMI) (Hashemzadeh et al, 2022). This suggests that factors beyond BMI, such as lifestyle and diet, may contribute to the increased cardiometabolic risk in food-insecure individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The association between food insecurity and cardiometabolic risk factors was explored in a study conducted in Iran (Hashemzadeh et al, 2022). The study found that cardiometabolic risk factors, such as blood glucose, triglycerides, total, HDL, and LDL cholesterols, and metabolic syndrome score, were associated with food insecurity independent of body mass index (BMI) (Hashemzadeh et al, 2022). This suggests that factors beyond BMI, such as lifestyle and diet, may contribute to the increased cardiometabolic risk in food-insecure individuals.…”
Section: Resultsmentioning
confidence: 99%